ANALISIS KELAYAKAN INVENTORY ASSET FOOD AND BEVEREAGE SERVICE TERHADAP PENGEMBANGAN STANDAR OPERASIONAL PROSEDUR PELAYANAN PADA HOTEL PUSAKO BUKITTINGGI - Fedri, Raftul (Menara Ilmu, 2019)
The service procedure at the restaurant is operational before the restaurant isopened until the restaurant is closed. This activity includes all the business of restaurantstaff in providing services to guests, both preparation of guests arriving until guests leavethe restaurant. To support success in carrying out tasks, a restaurant clerk must know andunderstand work procedures when food and beverage services take place. The workguidelines or standards referred to above are known as the Standard Operating Procedure(SOP Restaurant) which is supported by equipment that is in accordance with the standardand complete.This study aims to determine the type of restaurant equipment that supports thesmooth service to guests at the Pusako Bukittinggi hotel. Success during a restaurantoperates depending on how the restaurant clerk can do the job well. This work concernshow officers serve guests so that guests feel satisfied and happy for the service they get.By using qualitative assessment, it can be seen the forms of equipment that are inthe Food and Beverage Service division at the Pusako Hotel are used and coordinationbetween employees in preparing food service to guests.Keywords: Food and Beverage Service Equipment, Restaurant Service